THE CLARITY OF BUSINESS MODELS IN INTEGRATED ACCOUNTING REPORTS - Donleavy, Gabriel (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
In this study, 664 students enrolled in accounting theory courses at both the undergraduate and postgraduate levels at the University of New England were tasked with the assignment of critically assessing the decision usefulness and understandability of 2 to 4 integrated accounting reports. A key aspect of their analysis involved a critical examination of how the accounting reports conveyed the business models employed by the respective companies. In the case of consolidated reports, students were expected to observe distinct business models for each segment of the group or identify a robust rationale if only one model was presented. A team comprising both students and faculty examined all submitted reports, coding the embedded models for their complexity and understandability. The ensuing analysis revealed three distinct clusters of models, categorized as simple, orthogonal, or spread. The decision usefulness of these models exhibited significant variation and demonstrated a clear association with their understandability. Given that South Africa is the sole country mandating integrated accounting, a distinctive expectation was formed. Reports from South African corporations were anticipated to exhibit a degree of isomorphism or clustering around a specific model to a notably greater extent than reports from other countries. However, contrary to expectations, no such clustering was identified. Furthermore, it was anticipated that students would more accurately code simple business models, given their inherent simplicity and ease of comprehension. This expectation found substantial support in the results. Finally, the study hypothesized that spread models would be more prone to being cluttered by extravagant claims, messianic declarations, and legitimation discourses compared to simple models. This hypothesis received confirmation through the study's findings.